Labor market reform and innovation: Evidence from Spain - María García-Vega; Richard Kneller; Joel Stiebale (Heinrich Heine University Düsseldorf, Düsseldorf Institute for Competition Economics (DICE), 2020)
We analyze the effect of a labor market reform on firms' product innovation. The re- form, which amounts to a natural experiment, differentially reduced firing costs for some firms, thereby lowering adjustment costs in the presence of demand uncertainty. Using a difference-in- differences framework, we show that the reform increased product innovations. We also provide evidence that the reform induced upgrading of product quality and enabled firms to grow faster and enter new markets. The effects are concentrated in industries with high levels of demand volatility and R&D intensity, where exible adjustments to unexpected shocks are important.
Keywords: D22; J3; O31; G31; 330; Innovation; New products; Productivity; Labor market reform; EPL